Occurrence of Tetracycline Residue in Table Eggs and Genotoxic Effects of Raw and Heated Contaminated Egg Yolks on Hepatic Cells - Abbas KAMALI; Maryam MIRLOHI; Mahmod ETEBARI; Sohila SEPAHI (Tehran University of Medical Sciences, 2020)
Background: This study measured tetracycline residue in table eggs sampled from Isfahan markets in 2015 and assessed the toxic effects of heated egg yolk on hepatic cells Methods: Forty commercial and six locally produced eggs were randomly collected and tested for tetracycline resides using competitive ELISA with a mean recovery value of 65.22% and limit of detection (LOD) of 4 ng/g. For the seven most contaminated samples, albumen and yolk were examined individually and, despite the very low detected level in the yolk, the samples were subjected to boiling for 10 min. Finally, the DNA damaging properties of the raw or treated egg yolks on hepatic cells were investigated using the comet assay. Results: The residue levels ranged from <LOD to 9.77 ng/g with a mean value of 4.95 ng/g, which was far below the maximum residue level (MRL) of tetracycline in eggs (200 ng/g) established by the EFSA. The concentration of tetracycline residue in the albumin and yolk of the seven most contaminated samples was 4.75 ng/g and 6.83 ng/g, respectively, while boiling reduced it by 20%. Heat treatment induces DNA damage in HepG2 cells. Heating resulted in a marked increase in the comet length, % DNA in the tail, and tail moment parameters by 60%, 3000%, and 5000%, respectively. Conclusion: Despite the low concentration of tetracycline residue in samples, heat treatment can create degenerative compounds from tetracycline that can cause DNA damage in an in vitro model.